2004
DOI: 10.2176/nmc.44.558
|View full text |Cite
|
Sign up to set email alerts
|

Terminal Syringomyelia: Is It As Innocent As It Seems?-Case Report-

Abstract: A 5-day-old newborn girl presented with cutaneous signs of hypertrichosis, skin dimple, and subcutaneous lipoma in the lumbar region. Magnetic resonance (MR) imaging of the thoracolumbar spine demonstrated spinal dermal sinus, type II split cord malformation, and tethered cord. A small terminal syringeal cavity was also present. Five months after the diagnosis, weakness in dorsal flexion of the bilateral feet and toes was detected. Surgery to untether the cord was performed. Her deficits resolved completely. N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…2 If symptoms do not improve or the syrinx enlarges, placement of a syringosubarachnoid shunt is an effective treatment. 3,6,8 Intraoperative sonography can be used to guide for shunt placement. 2,3,6,8 Even when optimally placed, subarachnoid shunts are still subject to malfunction, with the most common being shunt obstruction, followed by injury to or tethering of the spinal cord, infection, and low-pressure CSF state.…”
Section: 7mentioning
confidence: 99%
See 1 more Smart Citation
“…2 If symptoms do not improve or the syrinx enlarges, placement of a syringosubarachnoid shunt is an effective treatment. 3,6,8 Intraoperative sonography can be used to guide for shunt placement. 2,3,6,8 Even when optimally placed, subarachnoid shunts are still subject to malfunction, with the most common being shunt obstruction, followed by injury to or tethering of the spinal cord, infection, and low-pressure CSF state.…”
Section: 7mentioning
confidence: 99%
“…3,6,8 Intraoperative sonography can be used to guide for shunt placement. 2,3,6,8 Even when optimally placed, subarachnoid shunts are still subject to malfunction, with the most common being shunt obstruction, followed by injury to or tethering of the spinal cord, infection, and low-pressure CSF state. 8 Most patients treated with shunting procedures will experience neurological improvement of symptoms with complete or mild regression of the syrinx.…”
Section: 7mentioning
confidence: 99%
“…4 Previous studies have suggested that terminal ventriculostomy causes TCS relapse, which may be due to reclosure of the fistula and preclude further drainage. [4][5][6] Conversely, Beaumont et al confirmed the advantages of this approach. 7 Thus, the effectiveness of terminal ventriculostomy remains controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Although many theories have been proposed regarding the formation and progression of syringomyelia, the underlying pathogenesis remains unknown. 5,7 Syringomyelia can occur posttrauma and may be associated with Chiari's malformations, intramedullary tumors, meningomyelocele, meningocele, or TCS. It typically occurs in the cervical and/or thoracic segments.…”
Section: Introductionmentioning
confidence: 99%